The Relationship between Learning Motivation and Self-Regulated Learning with Online Game Addiction of Junior High School Students - Julisia, Nindya; Nursalim, Mochamad (IKIP Siliwangi, 2025)
This study aims to determine the relationship between learning motivation with self-regulated learning and online game addiction of students at SMP Negeri 59 Surabaya. This study used a quantitative method with a correlation model; the research sample amounted to 229 students. The results of the correlation analysis between the three variables are <0.001, and the correlation coefficient value is 0.785, which means a positive relationship exists between learning motivation, self-regulated learning, and online game addiction. The study's conclusion reveals a relationship between learning motivation with self-regulated learning and online game addiction of students at SMP Negeri 59 Surabaya, which shows a positive and significant relationship. Learning motivation is high, then self-regulated learning and online game addiction are high. This research contributes to designing effective learning programs that utilize technology, such as educational games, that can increase learning motivation and reduce the potential for non-educative game addiction.